(untitled) (Research, Society and Development, 2022)
Penile cancer is a rare tumor with a higher incidence in men over 50 years of age. Total or partial penectomy is the most indicated treatment. This surgery is very complex, and requires specialized care from the pre to the post-operative period, followed by great care or surveillance, requiring family support. Method: This is an integrative review study, evidence-based practice resources, which brings the past empirical or theoretical literature and an understanding of the best available evidence on the practical knowledge of professionals described in literature (Broome, 2000). Having as objective definition, to establish inclusion and exclusion criteria for the selection of samples, information of selected articles, analysis and discussion of the results. To better guide this study, the strategy (PICO) was used to formulate the guiding questions of this integrative literature review, using descriptors in Portuguese and Spanish. The article is based on information from the literature and makes a case study about the personal perspective of an oncology nurse about the recovery of a patient affected by penectomy.